The Binding Nature of International Human Rights Court Judgments in Peru: An Interpretation of Article VIII of the New Constitutional Procedural Code - Villanueva Bazán, Marcelo; Castillo Córdova, Luis (Revista de Derecho, 2025)
The most recent amendment to Article VIII of the Preliminary Title of the New Constitutional Procedural Code introduces a change in the wording of the provision concerning the binding nature of international human rights court judgments with respect to the Peruvian State. This legal provision requires an interpretation that allows for the formulation of a constitutionally valid legal norm. Through constitutional interpretation and an analysis of the Peruvian legal framework regarding the binding force of international human rights court judgments, this paper seeks to determine what possible meanings may be attributed to the aforementioned provision and whether, under any of them, its constitutionality can be justified.